What is German ‘Angst’ (fear/anxiety)? A corpus approach based on frame analysis - Ni Yan; Marcus Müller (Language and Cognition)
The study employs a corpus-based frame analysis, grounded in Barsalou’s frame notion, as a complementary methodological approach to metaphor analysis for studying emotion concepts. We examine the conceptualization of the German ‘Angst’, which is widely recognized as a uniquely German emotion concept, yet it remains insufficiently studied. Through a systematic analysis of linguistic patterns, this study reconstructs the frame structure of ‘Angst’ based on 200,319 instances extracted from newspaper and social media data. The findings show that ‘Angst’ arises from diverse factors, including threats to life and health, prosperity, status, identity, power, relationships and the need for certainty and stability. There is an awareness and acceptance of ‘Angst’, reflected in the openness to expressing personal fear and addressing the fear of others in media discourse. When contextualized within insights from other disciplines, it becomes evident that the ‘Angst’ is rooted in universal biological foundations while also shaped by Germany’s sociohistorical context. Furthermore, it exhibits both alignment with and divergence from its philosophical conceptualization. These insights expose ‘Angst’ as both a psychological and cultural construct and demonstrate the advantage of combining frame analysis with corpus linguistic methods in capturing the specific structures of emotion concepts from large-scale data.